Dampak Penggunaan Pinjaman Online pada Kesejahteraan Keluarga Perspektif Maqāṣid al-Syarī‘ah - Sagina Sagina; Fitria Fitria; Nur Heppi Nelsiani (CV Global Research Publication, 2025)
This study aims to comprehensively analyze the impact of online loan utilization on family welfare in West Kalimantan Province using the analytical framework of maqāṣid al-sharī‘ah. The research employs a qualitative approach with a descriptive-analytical design, integrating normative literature review and empirical-sociological data. The findings reveal that a significant disparity between financial inclusion and financial literacy has fostered consumptive and manipulative borrowing patterns. The impacts include financial bankruptcy, escalating domestic conflicts leading to divorce, and severe psychological distress resulting from exploitative debt collection practices. The maqāṣid al-sharī‘ah analysis confirms that exploitative online loan practices contradict the principles of protecting wealth (ḥifẓ al-māl), family (ḥifẓ al-nasl), intellect (ḥifẓ al-‘aql), and life (ḥifẓ al-nafs). Therefore, holistic regulatory, educational, and cultural interventions are urgently required to mitigate the destructive impacts of online loans and to strengthen family resilience based on Islamic economic values.